Serial or parallel? Using depth-of-processing to examine attention allocation during reading. - Reichle ED; Vanyukov PM; Laurent PA; Warren T; Reichle, Erik D; Vanyukov, Polina M; Laurent, Patryk A; Warren, Tessa (Vision Research, 2008)
This paper presents an experiment investigating attention allocation in four tasks requiring varied degrees of lexical processing of 1-4 simultaneously displayed words. Response times and eye movements were only modestly affected by the number of words in an asterisk-detection task but increased markedly with the number of words in letter-detection, rhyme-judgment, and semantic-judgment tasks, suggesting that attention may not be serial for tasks that do not require significant lexical processing (e.g., detecting visual features), but is approximately serial for tasks that do (e.g., retrieving word meanings). The implications of these results for models of readers' eye movements are discussed.